Pengaruh Pembelajaran Tipe Jigsaw Pada Mata Pelajaran Bahasa Indonesia Kelas X SMA Negeri 18 Bone - Irwandi Irwandi; Syarifnur Syarifnur; A. Suharman (Journal on Education, 2024)
This research is an educational study that aims to highlight the effectiveness of using multimedia in the learning process. The type of research conducted is ex post facto, which means it is carried out after the event, by collecting data through surveys. The research was carried out at SMA Negeri 18 Bone, Bone Regency, with a population of all class X students, and a total sample of 28 people. The research instrument consists of a questionnaire and documentation. Data collection was carried out by distributing questionnaires to students directly. Data analysis uses descriptive analysis methods. The results of the research concluded that the influence of Jigsaw type learning on Indonesian language subjects in class Meanwhile, for indicators of fatigue and the community environment, the influence is in the low category.